Qualities of the propagator and keys to successful spreading of Islamic dakwah through alternative medicine - ElSayed, Khaled Abdelhay; Othman Talib; Abdul Ghafar Don (Institut Islam Hadhari Universiti Kebangsaan Malaysia, 2013)
This article studies the qualities that an alternative medicine practitioner should have to successfully treat patients and invite them to Islam. The researchers suggest a number of qualities for the practitioner to cure patients and invite them to embrace the religion through wisdom and beautiful preaching. These qualities include having knowledge based on belief and following, having knowledge of the methods and types of treatment, doing good deeds which make the practitioner a role model, prorogating Islam by knowing its aims and keys for its success among patients, and finally the virtue of patience which is important for both the practitioner and patient. The researchers also studied the keys to successful preaching of Islam through alternative medicine. Some of the qualities that both the practitioner treating by Alroqia and the patient should have, are also mentioned. The researchers also suggest that the practitioner should follow some important steps when treating the patients and should avoid committing mistakes. They conclude by noting the elements of success in disseminating Islam through alternative medicine. The methodology followed by the researchers was to review the previous sources and references in the field of alternative and Islamic medicine, as well as in the field of Islamic dakwah.